2010
DOI: 10.3109/0142159x.2010.490281
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and feedback to facilitate self-directed learning in clinical practice of Midwifery students

Abstract: Background: Clinical workplaces are hectic and dynamic learning environments, which require students to take charge of their own learning. Competency development during clinical internships is a continuous process that is facilitated and guided by feedback. Limited feedback, lack of supervision and problematic assessment of clinical competencies make the development of learning instruments to support self-directed learning necessary. Aims: To explore students' perceptions about a newly introduced integrated fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 25 publications
3
28
1
2
Order By: Relevance
“…We expect this information to help assessors in making their summative judgements. However, we found contradicting results when analysing qualitative perceptions of learners (Embo et al, 2010(Embo et al, , 2014b and quantitatively significant correlation scores between reflection ability and performance . Students' perceptions about summative assessment can be translated into students' concerns about subjectivity of assessments.…”
Section: How Well Does the Model Workcontrasting
confidence: 91%
See 1 more Smart Citation
“…We expect this information to help assessors in making their summative judgements. However, we found contradicting results when analysing qualitative perceptions of learners (Embo et al, 2010(Embo et al, , 2014b and quantitatively significant correlation scores between reflection ability and performance . Students' perceptions about summative assessment can be translated into students' concerns about subjectivity of assessments.…”
Section: How Well Does the Model Workcontrasting
confidence: 91%
“…Students' perceptions about summative assessment can be translated into students' concerns about subjectivity of assessments. We found that learners want to engage more in feedback-dialogues with their supervisors (Embo et al, 2010(Embo et al, , 2014b. We argue that longitudinal internships, with longer student-teacher relationships, can optimise collaborative and continuous learning (Teherani et al, 2013).…”
Section: How Well Does the Model Workmentioning
confidence: 88%
“…As with peer-assessment, some researchers noted that self-assessment can be time-consuming (Bedford & Legg, 2007;Embo, Driessen, Valcke, & Van der Vleuten, 2010;McDonnell & Curtis, 2014;Pain & Mowl, 1996), that Note. Individual papers frequently targeted more than one recipience process and/or involved more than one intervention component.…”
Section: Internalizing and Applying Standardsmentioning
confidence: 99%
“…En cuanto a la percepción de los alumnos, hubo mejoría en todos los ítems evaluados en el período post intervención, destacando las áreas de Notas, Feedback y Nota global. Es llamativo notar que los alumnos reportaron una mayor dedicación al curso en tiempo, siendo el período asignado al CTG igual en ambos programas, reflejando un mayor tiempo dedicado al aprendizaje independiente basado en autoinstructivos, en función de sus necesidades individuales identificadas en el proceso de revisión de las pruebas 1 y 2 (feedback inmediato, estructurado, sistemático) 19 . Las evaluaciones intermedias con posterior corrección fueron bien recibidas, ya que al tener una pequeña ponderación en la nota final, los alumnos se veían incentivados a estudiar.…”
Section: Discussionunclassified